2016
DOI: 10.2497/jjspm.63.63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxide Particles inside Iron Powders on Hardness and Coercivity of Soft Magnetic Composite Cores

Abstract: Soft magnetic composite (SMC) cores, produced by compacting insulated iron powders, are expected to improve the efficiency of motors and boost converters. Low-cost water atomized iron powders are used as raw materials for SMC cores. Since the water atomized iron powders containing a large amount of oxygen impurity, there is a problem that the magnetic properties of the SMC cores are deteriorated due to oxygen impurity. First, green compacts were made by several kinds of water atomized iron powders in which oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Under an assumption that H c_ex is constant, the constants £ and H c_ex are estimated from the experimental results of H c , d i and μ. Actually, the assumption is reasonable in this study, because the causes of H c_ex , such as the inclusions 4) and void space between particles 13) are identical for all of the specimens prepared from the same raw material prepared through the same compaction process and conditions. The value of H c ¹ 1.3 © 10 ¹3 /d i calculated from the experimental results are plotted against μ in Fig.…”
Section: Influence Of Plastic Deformation On Coercive Force Ofmentioning
confidence: 97%
See 1 more Smart Citation
“…Under an assumption that H c_ex is constant, the constants £ and H c_ex are estimated from the experimental results of H c , d i and μ. Actually, the assumption is reasonable in this study, because the causes of H c_ex , such as the inclusions 4) and void space between particles 13) are identical for all of the specimens prepared from the same raw material prepared through the same compaction process and conditions. The value of H c ¹ 1.3 © 10 ¹3 /d i calculated from the experimental results are plotted against μ in Fig.…”
Section: Influence Of Plastic Deformation On Coercive Force Ofmentioning
confidence: 97%
“…Moreover, crystal grain size in a pure iron powder core after annealing increases with an increase in the circularity of the base iron powder because of a decrease in the dislocation density induced during compaction. Nishi et al 4) have reported the influence of oxide particles on the coercive force of pure iron powder cores, and concluded that coercive force increases with an increase in the number of oxide particles per unit volume.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined the relationship between pinning sites and the coercive force of iron powder cores. Nishi et al 4) focused on inclusions as pinning sites and reported an increase in coercive force with an increase in the number of oxide particles per unit volume of a pure iron powder core. Tajima et al 5) also confirmed a decrease in hysteresis loss with a decrease in porosity in an iron powder core, suggesting that porosity has some effect on coercive force.…”
Section: Introductionmentioning
confidence: 99%